Pengaruh Green Finance dan Profitabilitas Terhadap Nilai Perusahaan dengan Good Corporate Governance Sebagai Moderasi - Nurul Ifadhoh; Puji Endah Purnamasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study analyzes the effect of Green Finance and profitability on firm value with Good Corporate Governance (GCG) as a moderating variable. In the context of globalization, firm value reflects financial performance and market perceptions of a company's capabilities. The method used is a quantitative approach with panel data analysis, using secondary data from the annual reports of companies listed on the Indonesia Stock Exchange during 2020-2023. The results indicate that Green Finance does not significantly influence corporate value, while profitability has a positive effect. GCG, as a moderating variable, is not sufficiently strong to moderate the influence between Green Finance and profitability on corporate value. These findings emphasize the need for further evaluation of the effectiveness of implementing Green Finance and GCG in creating corporate value recognized by the market.